Brief fixation enables same-day breast cancer diagnosis with reliable assessment of hormone receptors, E-cadherin and HER2/Neu. Issue 9 (21st March 2017) - Halilovic, Altuna; Bulte, Joris; Jacobs, Yvonne; Braam, Hanneke; van Cleef, Patricia; Schlooz-Vries, Margrethe; Werner, Annelies; Boelens, Oliver; Nagtegaal, Iris; de Wilt, Hans; Bult, Peter
Abstract : Aims: Preoperative core needle biopsy (CNB) is commonly used to confirm the diagnosis of breast cancer. For treatment purposes and for determining histological type, especially in case of neoadjuvant therapy, oestrogen receptor (ER), progesterone receptor (PR), human epidermal growth factor receptor 2 (HER2) status and E-cadherin assessments are crucial. Considering the increasing demand for same-day diagnosis of breast lesions, an accelerated method of CNB processing was developed, in which the tissue fixation time is radically reduced. Methods: To determine whether short fixation time frustrates assessment of ER, PR and E-cadherin immunohistochemistry (IHC) and HER2 fluorescence in situ hybridisation (FISH), 69 consecutive patients with 70 invasive breast carcinomas were included through the same-day diagnostics programme of breast lesions of the Radboud university medical center and the hospital Pantein. IHC for ER, PR and E-cadherin and HER2 FISH were compared between CNBs fixed for approximately 60–90 min and traditionally fixed resection specimens. Results: Overall agreement between CNBs and resection specimens was 98.6% for ER (p<0.001; κ=0.93), 90.0% for PR (p<0.001; κ=0.75), 100% for E-cadherin (p<0001; κ=1.00) and 98.6% (p<0.001; κ=0.94) for HER2 FISH. Positive and negative predictive values were respectively 98.4% and 100% for ER, 95.9% and 76.2% for PR, 100% and 100% for E-cadherin and 90% and 100% for HER2 FISH. Conclusions: Hormone receptors and E-cadherin IHC and HER2 FISH are highly comparable between briefly fixed CNBs and the corresponding traditionally fixed resection specimens, and can therefore reliably be used in the daily clinical practice of same-day diagnostics of breast cancer.